Comparison of Creatine Kinase Myocardial Band (CK-MB) and High Sensitive Troponin I (hsTnI) Values Between Athletes and Sedentary People - Çakaroğlu, Deniz; Kaya, Mustafa Oğuzhan (Progress in Nutrition, 2020)
Study Objectives: This study was conducted to examine and compare CK-MB and hsTnI values between people who exercise regularly and actively and those who do not, considering that men have a higher muscle mass than women, but also the higher amount of estrogen secreted in women. Methods: The test group was composed of 18 men, 17 women, a total of 35 (23.28±4.09 years) persons who engaged in active sports with no problems in terms of blood measurement. The control group was formed from a total of 34 (24.50±5.60 years) persons, including 17 men and 17 women with a sedentary lifestyle that do not engage any sport. Statistical analyses were evaluated in the SPSS program and the Independent Samples t Test was used to determine the difference between the groups. Results: The CK-MB values of active athletes were found to be less than 5 U/L (1.95±1.04), which is the mean value, and higher values than the control group. hsTnI values have a significant difference between the test group and the control group and this difference was found to below the middle level. The mean CK-MB and hsTnI values of men participants were found to be statistically significant, with more than the mean value of women participants. The men test group CK-MB values were found to be higher than the control group and there was a significant difference (p